The Role of Wildlife Corridors in Maintaining Biodiversity and Ecosystem Services - Nam, Le Hoang; Anh, Nguyen Tuan; Mai, Nguyen Thi (Journal of Selvicoltura Asean, 2024)
Wildlife corridors are critical for maintaining biodiversity and ecosystem services, especially in fragmented landscapes. These corridors facilitate species movement, promote genetic diversity, and enhance ecosystem resilience. Understanding their role is essential for effective conservation strategies in the face of habitat loss and climate change. This research aims to assess the effectiveness of wildlife corridors in supporting biodiversity and providing essential ecosystem services. The study seeks to identify key factors influencing the success of these corridors and their impact on wildlife populations and ecosystem health. A mixed-methods approach was employed, combining quantitative data from ecological surveys with qualitative insights from stakeholder interviews. Field studies were conducted in various ecosystems with established wildlife corridors, focusing on species movement patterns, population dynamics, and ecosystem service assessments. Findings indicate that wildlife corridors significantly enhance biodiversity by facilitating species dispersal and reducing isolation. The study revealed increased species richness and improved ecosystem services, such as pollination and seed dispersal, in areas connected by corridors. Stakeholder feedback highlighted the importance of community involvement in corridor management. This study concludes that wildlife corridors play a vital role in maintaining biodiversity and enhancing ecosystem services. Effective management and community engagement are essential for the success of these corridors. Policymakers and conservationists must prioritize the establishment and maintenance of wildlife corridors to mitigate the impacts of habitat fragmentation and support ecological health.